Experimental investigation on a cropped delta wing with edge blowing - Alexander, A. J. (College of Aeronautics, 1963)
Low speed wind tunnel tests have been made on a 70° cropped delta wing with edge blowing both in the plane of the wing and at a downward deflection angle of 30°. The tests include six-component force and moment measurements, the distribution of static pressure at four chordwise stations, and quantitative measurements of the flow in the leading edge vortex. At a constant incidence, blowing increases the size and strength of the leading edge vortices and moves the vortex cores outwards and upwards. Blowing also tends to suppress the secondary separation due to the entrainment effect of the jet. Blowing from the streamwise tips and trailing edge was relatively ineffective and most of the tests were made with blowing from the swept leading edges only, with tips and trailing edge sealed.